Molecular mechanism study on the contribution of open-fire flue-curing technology to tobacco leaf aroma - Kaiyuan Gu; Jialiang Li; Lu Zhao; Jiaen Su; Xu Wei; Xianglu Liu; Binbin Hu; Yonglei Jiang; Yi Chen (Chemical and Biological Technologies in Agriculture)
Abstract This study compared the effects of open-fire flue-curing and conventional curing methods on the aroma and chemical composition of K326 tobacco leaves, aiming to reveal the molecular mechanisms of aroma formation during open-fire flue-curing. The results showed that after curing, the leaves from conventional curing appeared orange-yellow, while those from open-fire flue-curing exhibited a brownish color. Sensory evaluation indicated that the leaves absorbed the combustion aroma of pine wood, resulting in an elegant woody fragrance, enhanced pungency, and a harmonious balance between the pungency and woodiness, with a rich aroma and prominent flavor. Physical and chemical analyses indicated that, Unlike conventional curing, the rate of moisture loss in open-fire flue-cured leaves was slower. Between 38 °C and 42 °C, the moisture content of conventionally cured leaves decreased by 9.96%, while that of open-fire flue-cured leaves decreased by only 5.18%. Meanwhile, during this phase, the activity of polyphenol oxidase (PPO) in open-fire flue-cured leaves was significantly higher than in conventionally cured leaves. Phenolic compound analysis showed that, Compared to conventional curing, the scopolamine content in open-fire cured leaves decreased by 33.85%, while the contents of neochlorogenic acid, chlorogenic acid, and rutin increased significantly to 1.63, 11.59, and 16.46 mg/g, respectively. An integrated metabolomics and proteomics analysis identified phenylalanine metabolism and amino acid degradation pathways as the central mechanisms driving aroma differentiation. Specifically, key enzymes and proteins in the phenylalanine metabolism pathway were significantly upregulated, promoting the synthesis of phenylalanine and its derivatives. Meanwhile, the degradation of lysine resulted in the conversion of fewer nitrogen-containing compounds in the open-fire flue-cured leaves. These synergistic effects enhanced the production of secondary metabolites, which were further released and transformed during the curing process, ultimately improving the aroma quality of the tobacco leaves. This study not only deepens the scientific understanding of aroma formation during open-fire flue-curing, but also provides theoretical support for the precise regulation and directional synthesis of characteristic aromas, offering feasible strategies to optimize curing processes and enhance the industrial quality of tobacco. Graphical Abstract